Functional traits of three major invasive grasses in a threatened tropical mountain grassland - FERNANDES, GERALDO W.; TAMEIRÃO, LUCAS B.S.; COSTA, ADRIANA R.; RIBEIRO, DANIELE G.; NEVES, MICHELE N.; BRITO, BETÂNIA G. SOUZA E; NEGREIROS, DANIEL (Anais da Academia Brasileira de Ciências, 2021)
The native flora of the Brazilian rupestrian grassland (campos rupestres) is threatened by the spread of invasive grasses. In this study, we evaluated the effect of habitat on the functional traits and CSR ecological strategies of three invasive alien grasses occurring both in the ironstone (IRG) and quartzitic (QRG) rupestrian grassland habitats. Although in both habitats the invasive species predominantly showed a stress-tolerant strategy, they exhibited distinct degrees of stress-tolerance and slightly differences in functional traits values in the IRG compared to the QRG. Habitat type distinctly influenced invasive grasses functional traits and ecological strategies, revealing a species-specific pattern.The native flora of the Brazilian rupestrian grassland (campos rupestres) is threatened by the spread of invasive grasses. In this study, we evaluated the effect of habitat on the functional traits and CSR ecological strategies of three invasive alien grasses occurring both in the ironstone (IRG) and quartzitic (QRG) rupestrian grassland habitats. Although in both habitats the invasive species predominantly showed a stress-tolerant strategy, they exhibited distinct degrees of stress-tolerance and slightly differences in functional traits values in the IRG compared to the QRG. Habitat type distinctly influenced invasive grasses functional traits and ecological strategies, revealing a species-specific pattern.